WCDMA in Malaysia - Mohamad, Alias (Penerbit UTM, 2008)
Wideband Code Division Multiple Access (WCDMA) A 3G highspeed digital data service provided by cellular carriers that use the time division multiplexing (TDMA) or GSM technology worldwide, including AT&T (formerly Cingular) and T-Mobile in the U.S. WCDMA works on WCDMA cell phones as well as laptops and portable devices with WCDMA modems [1]. Users have typically experienced downstream data rates up to 400 Kbps [1]. WCDMA has been used in the Japanese Freedom of Mobile Multimedia Access (FOMA) system and in the Universal Mobile Telecommunications System (UMTS); a third generation follow-on to the 2G GSM networks deployed worldwide [1]. Although TDMA and GSM carriers both use TDMA modulation, WCDMA stems from CDMA. Part of the 3GPP initiative, the International Telecommunication Union (ITU) refers to WCDMA as the Direct Sequence (DS) interface within the IMT-2000 global 3G standards [1].